Pemanfaatan Jerami Padi dan Arang Sekam sebagai Pupuk Organik dan Media Tanam dalam Budidaya Kedelai - Aprilia Ike Nurmalasari; Supriyono Supriyono; Maria Theresia Sri Budiastuti; Trijono Djoko Sulistyo; Sri Nyoto (Universitas Sebelas Maret, 2021)
Composting of Rice Straw for Organic Fertilizer and Manufacturing Rice Husk Charcoal as Planting Medium in Soybean Demonstration Plot. Agricultural waste is the residue from an agricultural business activity, which if left unchecked can have a negative impact on the environment. Agricultural waste such as rice straw can be used for organic fertilizers because it has high potassium and lignin content. The purpose of this community service activity is to increase the knowledge and skills of the community and farmers about straw processing through the composting stage as organic fertilizer and burning rice husks into husk charcoal as a planting medium in soybean cultivation. Community service was carried out from July to August 2020 in Pengkok Village, Kedawung District, Sragen Regency, namely in the Subur and Sumber Agung farmer groups. Community service activities carried out are counseling or socialization of the use of straw and husk charcoal as organic fertilizer and planting media, then proceed with demonstrations or practices for making organic fertilizers and husk charcoal which are continued with planting soybeans in polybags with the application of compost and husk charcoal that have been made. The result of this service activity is that participants or farmer groups can make organic fertilizer from straw waste and husk charcoal independently and can be applied when cultivating soybeans in polybags as well as understanding the stages of making straw compost and burning husks into husk charcoal. The conclusion from the service activities that have been carried out is the understanding of the knowledge of community service participants about the methods or stages of composting in making organic fertilizer and making husk charcoal from rice husk waste for planting media as proven by farmers being able to make organic fertilizer from rice straw which initially becomes waste that is not optimal. used as compost which is made through the composting stage and the manufacture of husk charcoal using the burning method in a funnel and then applied in the soybean demonstration plot experiment in polybags.